A subject-specific finite element model of the anterior cruciate ligament - Zhang, Xiaoyan; Jiang, Guotai; Wu, Changfu; Woo, Savio L-Y. (2008 30th Annual International Conference of the IEEE Engineering in Medicine and Biology Society, 2008)
The anterior cruciate ligament (ACL) is commonly injured. The stress distribution in the ACL is the key for understanding its function and injury mechanism, as well as for developing optimal surgical reconstruction protocols. In this study, a three-dimensional subject-specific finite element model of human ACL was developed. Bony geometries were reconstructed from CT scan images, while the geometry of the ACL and the orientation of its fiber bundles were measured via a mechanical digitizer. A transversely isotropic, hyperelastic, and nearly incompressible constitutive model was implemented to describe the mechanical properties of the ACL. A 134N anterior tibial load were applied to a cadaveric knee specimen at full extension, 30°, and 60° of flexion by a 6-DOF Robotic/Universal Force-moment Sensor (UFS) system, which was also used to measure the ACL resultant force. Knee kinematics was collected by digitizing two registration blocks attached to the femur and the tibia, respectively, and was input into the FE model as boundary conditions. The resultant force of the ACL calculated by the FE model was comparable to the experimental data, with the error within 10%, thus validated the model. The FE results showed that the average stress in the ACL was between the range 4.7-5.0MPa, with a peak stress between the range 9.8-10.9MPa, which shifted from the posterior lateral (PL) bundle to the anterior medial (AM) bundle as the knee flexed.